Determination of anti-Toxoplasma gondii antibodies in cattle in Elazig and environs by Sabin-Feldman (SF) test - Aktas, M; Babür, C; Karaer, Z; Dumanli, N (Tubitak Scientific & Technological Research Council Turkey, 2000)
Toxoplasma gondii pseudocysts in cattle are sources of infection for humans. Therefore, cattle toxoplasmosis is a very important factor in public health. The aim of the present study was to determine the seroprevalence of cattle toxoplasmosis. A total of 122 cattle from different age groups were selected in Elazig and environs. Blood samples were taken and sera were collected. Serum samples were kept at -20 degreesC until further examination. The values of toxoplasmosis seroprevalence were determined by SF test for anti-Toxoplasma gondii antibodies. Antibodies were detected in 86 out of 122 cattle sera (70.49%). Fifty-four (62.75%), 26 (30.23%), 6 (6.97%) of seropositive cattle sera were positive when diluted at 1/16, 1/64, 1/256 respectively The seroprevalence values were 54.05% and 77.64% in the age groups of 0-1 and older than 1 year. There were statistical significant differences (p = 0.01) among the age groups.
Keywords: Toxoplasma gondii; cattle; SF